Flexible perovskite solar cells fabricated by a gradient heat treatment process. Issue 2 (9th December 2019) - Xiao, Yue Yue; Meng, Yongqiang; Gao, Hongli; Chen, Yichuan; Meng, Qi; Bai, Yanjie; Wang, Hao; Zhang, Yongzhe; Yan, Hui; Han, Chang Bao
Abstract : A gradient heat treatment process can effectively improve the quality of perovskite films and the efficiency of flexible perovskite solar cells. Abstract : Flexible perovskite solar cells (F-PSCs) are attracting tremendous research interest due to their light weight and flexibility. However, the poor quality of perovskite films caused by deformation of flexible substrates during a general heat treatment process hinders the fabrication of high efficiency flexible cells. Here, a simple gradient heat treatment (GHT) process is developed to effectively improve the crystal quality of perovskite films and the efficiency of F-PSCs. The results show that a smaller temperature fall-off gradient will be beneficial to the further growth of perovskite films, which helps to further enhance the crystalline quality. Compared with the conventional method, the power conversion efficiency (PCE) of F-PSCs fabricated by a GHT process with a relatively small gradient significantly improved by 31%, and the maximum PCE increased to 17.37%. This work provides a new idea for ameliorating the quality of perovskite films and enhancing the performances of F-PSCs.